ChemInform Abstract: Facile Development of Chiral Alkenylboranes from Chiral Diynes for Asymmetric Hydrogenation of Silyl Enol Ethers. Issue 27 (18th June 2015) - Ren, Xiaoyu; Li, Gen; Wei, Simin; Du, Haifeng
Abstract The metal—free asymmetric hydrogenation of silyl enol ethers is carried out using in situ generated chiral borane with the combination of tBu3P as catalyst.